FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR MENJADI AKUNTAN PUBLIC (Studi Empiris Pada Mahasiswa Akuntansi UR, UIN SUSKA, Di Pekanbaru Dan UNP, UNAND Di Padang) - Novrika Yanti; R.Adri Satriawan Surya; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
e accounting students in the selection of a public accounting career. Factors influencing the selection of a public accounting career with a variable measured the intrinsic value of work, salary, work environment, professional training, professional recognition, social values, labor market considerations, personality and academic attainment. The sample used by 120 respondents. Analysis of the data in this study usingmultiple regression analysis with SPSS version 20.The results of this analysis showed that variables intrinsic value of work, salary, work environment, professional training, professional recognition, social values, labor market considerations, personalities and academic attainment significant effect on career selection became public accountants by accounting students, but the partial variable work environment andacademic attainment does not significantly influence the selection of a career public accountants by accounting students, while variable intrinsic value of work, salaries, professional training, professional recognition, social values, labor market considerations, and the personality of each significant effect.Keyword : career selection became public accountant, public accounting profession, intrinsic value of work, salaries, work environment